2023
DOI: 10.1111/cdev.13906
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in the structure of shyness and internalizing symptoms from early to middle childhood: A network analysis

Abstract: Shyness is a temperamental trait that shares considerable conceptual overlap with aspects of internalizing problems, creating difficulties in operationalizing and assessing these two constructs and their association. This study addresses these issues by employing network analyses. Participants were, white, N = 555 children (Mage = 52.45 months, SD = 15.96, 55% girls) followed longitudinally over 4 years (2016–2010) in Norway. Teachers rated child shyness and assessed children's internalizing symptoms. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Previous research has also demonstrated gender differences in shyness, as well as in its associations with developmental outcomes (2, 45,46), although such differences have not been consistently reported (47,48). Studies also have shown parental socioeconomic factors to be associated with a variety of child outcomes (49, 50).…”
Section: The Present Studymentioning
confidence: 99%
“…Previous research has also demonstrated gender differences in shyness, as well as in its associations with developmental outcomes (2, 45,46), although such differences have not been consistently reported (47,48). Studies also have shown parental socioeconomic factors to be associated with a variety of child outcomes (49, 50).…”
Section: The Present Studymentioning
confidence: 99%
“…For example, s hyness (high approach; high avoidance) is characterized by an internal conflict between the desire to engage with others and socio-evaluative fears. Of note, shyness shares conceptual overlap (but is distinct from) anxiety (particularly social anxiety), which can also fuel solitary behavior ( 23 ). Next, social avoidance (low approach; high avoidance) is characterized by both a high desire to avoid others and a drive to be alone.…”
Section: Introductionmentioning
confidence: 99%